How work redesign interventions affect performance: An evidence-based model from a systematic review - Knight, Caroline; Parker, Sharon (SAGE, 2019)
It is not yet clear whether work redesigns actually affect individual-, team- or organizational-level performance. In a synthesis of this literature, we conclude there is good overall evidence, with the most promising evidence at the individual level. Specifically, our systematic review assessed whether top-down work redesign interventions affect performance and, if so, why (mechanisms) and when (boundary conditions). We identified 55 heterogeneous work redesign intervention studies, of which 39 reported a positive effect on performance, two reported a negative effect, and 14 reported mixed effects. Of five types of work redesign, the evidence that work characteristics can explain the effect of redesign interventions on performance was most promising for relational interventions, and participative and non-participative job enrichment and enlargement. Autonomous work group and system-wide interventions showed initial evidence. As to ‘why’ work redesigns enhance performance, we identified change in work motivation, quick response and learning as three core mechanisms. As to ‘when’, we showed that intervention implementation, intervention context (including alignment of organizational systems, processes and the work redesign) and person factors are key boundary conditions. We synthesize our findings into an integrative multilevel model that can be used to design, implement and evaluate work redesigns aimed at improving performance.